Analysis of The Potential and Challenges of Developing Bagasse as Bioethanol Fuel - Hanabell Jovanka; Fransisca Chiara Anindita (Diponegoro University, 2025)
Bioethanol is an alternative energy source to fossil fuels derived from plant materials containing cellulose, such as sugarcane bagasse. According to data from the Ministry of Energy and Mineral Resources of the Republic of Indonesia, fuel consumption in Indonesia reached 29.68 million kiloliters in 2022. Transportation contributes the largest share of emissions at 80%. This study will review the potential and challenges of increasing bioethanol use as a 15% blend in non-diesel fuels by 2025. The research utilizes secondary data to produce solutions addressing these issues, concluding the overall analysis. The use of sugarcane bagasse as a bioethanol feedstock offers several advantages over traditional fuels, including (1) reducing carbon monoxide emissions by 19-25%, (2) lowering fuel costs, and (3) increasing octane value. Despite these benefits, bioethanol utilization faces challenges such as (1) the need for further research, (2) the requirement for advanced and expensive technology, and (3) raw material availability. Presidential Instruction No. 1/2006 emphasizes the need for biofuels, making this review essential. The study identifies steps to maximize the potential of bioethanol in reducing emissions and minimizing challenges.